Room-temperature curing water-based ultrahigh-voltage insulating coating for electronics
By using water-based ultra-high voltage insulating coatings and modified composite nanoparticles to form a room temperature curing electronic insulating coating, it solves the problem of insufficient electrical insulation performance and stability of existing insulating materials and achieves efficient electrical insulation and external force resistance. ability.
Patent Information
- Application Number
- CN202411304957.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-21
AI Technical Summary
The electrical insulation performance of existing electronic and electrical insulating materials is relatively average, with poor external force resistance and poor structural stability, which cannot meet the long-term use needs.
A water-based ultra-high voltage insulating coating is used to form a room-temperature curing water-based ultra-high voltage insulating coating for electronics through room temperature curing. The coating is prepared from two components, A and B, including water-based polyurethane resin, insulating nanomaterials, etc., and is coupled with polydopamine and silane. The agent modifies titanium dioxide to form composite nanoparticles, improving the dispersion and electrical insulation properties of the material.
It significantly improves the electrical insulation properties and external force resistance of the coating, enhances the stability and long-term performance of the coating, and can maintain the ultra-high voltage insulation effect for a long time.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating processing, in particular to a room temperature curing water-based ultra-high voltage insulating coating for electronics. Background Art
[0002] Insulating coating is a coating with excellent electrical insulation. It has good electrical, thermal, mechanical and chemical properties. It is mostly varnish, but there are also colored paints. Insulating coatings are divided into two types: solvent-based with a temperature resistance below 600℃ and water-based with a temperature resistance of 600-1700℃. The coating can form a ceramic coating with a high volume resistivity on the surface of the coated object, which can withstand a strong electric field without being broken down. The coating has high mechanical strength and good chemical stability, and is resistant to aging, water and chemical corrosion; it also has mechanical shock and thermal shock resistance, and the coating can work continuously within the corresponding working temperature range.
[0003] For example, the invention patent with the announcement number CN112706480A discloses a method for preparing a polyurethane electronic and electrical insulating material, wherein the raw materials include polymerized fluororubber, polyurethane emulsion and a special auxiliary coating, wherein the polymerized fluororubber is composed of fluorine-containing monomer molecules, water, additives, dispersants, neutralizing buffers, initiators and chain transfer agents, and the special auxiliary coating includes a cold-resistant tough coating, an elastic coating and a wear-resistant coating, wherein the cold-resistant tough coating adopts a polyimide tough film, the elastic coating adopts an elastic coating, and the wear-resistant coating adopts a wear-resistant coating, and the raw materials are processed through the following processing steps to obtain a finished product; the preparation method of the polyurethane electronic and electrical insulating material, by using fluororubber as the main body, using the acetone method to self-emulsify the urethane emulsion and then polymerizing it with each other to form a modified fluororubber, so that the whole has good corrosion resistance, can adapt to high and low temperature environments, and improves its own cold and heat resistance to the extreme, greatly improving the overall work applicability; however, the electrical insulation performance of the insulating material is relatively general, and its resistance to external forces is poor, it is easy to break, and its structural stability is poor, and it cannot meet the needs of long-term use. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a room temperature curing water-based ultra-high voltage insulating coating for electronics.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A room temperature curable water-based ultra-high voltage insulation coating for electronics, wherein the coating is formed by curing a water-based ultra-high voltage insulation coating at room temperature;
[0007] The water-based ultra-high voltage insulating coating is prepared from two components, A and B;
[0008] Component A includes the following raw materials in parts by weight: 50-60 parts of waterborne polyurethane resin, 5-10 parts of curing agent, 3-7 parts of polyetheretherketone ultrafine powder, 8-13 parts of insulating nanomaterials, and 20-26 parts of water;
[0009] Component B includes the following raw materials in parts by weight: 1-2 parts of dispersant, 2-3 parts of antifoaming agent, 1-2 parts of leveling agent, 1-3 parts of wetting agent, 0.5-1.8 parts of film-forming aid, and 1-2 parts of thickener;
[0010] The preparation method of the water-based ultra-high voltage insulating coating comprises the following steps:
[0011] 1) stirring and mixing the waterborne polyurethane resin, polyetheretherketone ultrafine powder, insulating nanomaterial and water to obtain a mixture;
[0012] 2) The remaining raw materials are stirred and mixed, and then added into the mixture of step 1), and stirring is continued to obtain the water-based ultra-high voltage insulating coating.
[0013] As a further preferred embodiment of the present invention, the curing agent is at least one of cuprous sulfate and cuprous nitrate.
[0014] As a further preferred embodiment of the present invention, the preparation method of the insulating nanomaterial is as follows:
[0015] 1) Styrene containing 2-3% of divinylbenzene by mass, deionized water and anhydrous ethanol are mixed, stirred well, potassium persulfate is added, and the mixture is reacted at 75-78° C. for 3-6 hours. Pentafluorostyrene containing 2-3% of divinylbenzene by mass is then dripped into the reaction system using a constant pressure funnel within 30-40 minutes. The reaction is continued for 3-5 hours. After the reaction is completed, the product is repeatedly washed with anhydrous ethanol after centrifugation and vacuum dried to obtain fluorinated styrene microspheres;
[0016] 2) Put the basalt fiber into a Soxhlet extractor, use acetone to extract for 12-15 hours, then repeatedly wash with deionized water and dry to obtain pretreated basalt fiber, add the composite nanoparticles into a container containing anhydrous ethanol and deionized water to obtain a suspension, then add fluorinated styrene microspheres, add the pretreated basalt fiber after 200-300W ultrasonic oscillation for 30-50 minutes, soak at 50-56°C for 1-3 hours, and dry at 50-60°C for 5-10 hours to obtain an insulating nanomaterial.
[0017] Furthermore, in step 1), the usage ratio of styrene, deionized water, anhydrous ethanol, potassium persulfate and pentafluorostyrene is (10-16) g: (110-160) mL: (160-200) mL: (0.3-0.5) g: (8-12) g.
[0018] Furthermore, in step 2), the mass ratio of anhydrous ethanol to deionized water is (4.0-4.5):1;
[0019] The solid content of the suspension is 0.5-1.5%;
[0020] The added amount of the fluorinated styrene microspheres accounts for 0.2-0.6% of the total mass of the suspension.
[0021] As a further preferred embodiment of the present invention, the preparation method of the composite nanoparticles is as follows:
[0022] 1) Weigh titanium dioxide, disperse it in deionized water, stir and disperse it thoroughly, then add tris(hydroxymethyl)aminomethane hydrochloride and dopamine hydrochloride in sequence, stir at 25-28° C. for 4-6 hours, and after the treatment is completed, wash it repeatedly with deionized water, dry it, and grind it to obtain pretreated titanium dioxide;
[0023] 2) Silane coupling agent KH550, anhydrous ethanol and deionized water are weighed, stirred at 800-1000 r / min for 10-30 min at 60-63° C. to obtain a mixed solution, and then pretreated titanium dioxide is added, and magnetic stirring is continued at 80-85° C. and 600-700 r / min for 3-6 h. After the treatment is completed, the mixture is washed with deionized water, centrifuged, and dried to obtain modified titanium dioxide;
[0024] 3) Dissolve 1-2g of silane coupling agent KH550 and 2-5g of succinic anhydride in 60-80mL of N,N-dimethylformamide, stir at 80-85°C for 3-5h to obtain solution A, disperse 1-3g of nano-aluminum oxide in 60-80mL of N,N-dimethylformamide, ultrasonically disperse for 30-50min, then add 60-80mL of deionized water to obtain solution B, mix solution A and solution B in equal volumes, and stir magnetically at 40-45°C for 3-5h to obtain carboxylated aluminum oxide;
[0025] 4) Add carboxylated aluminum oxide to N,N-dimethylformamide, and after ultrasonic oscillation for 30-50 minutes, add it together with N,N-dicyclohexylcarbodiimide to silane coupling agent KH550, stir at 300-500 r / min for 3-7 hours at 40-43°C, then centrifuge and dry, and fully ball-mill with modified titanium dioxide in a mass ratio of 1: (0.3-0.8) to obtain composite nanoparticles.
[0026] Furthermore, in step 1), the ratio of the titanium dioxide, deionized water, tris(hydroxymethyl)aminomethane hydrochloride, and dopamine hydrochloride is (10-15) g: (200-300) mL: (0.3-0.4) g: (0.1-0.2) g;
[0027] The stirring speed is 8000-10000 r / min.
[0028] Furthermore, in step 2), the usage ratio of the silane coupling agent KH550, anhydrous ethanol, deionized water, and pretreated titanium dioxide is (1-3) mL: (90-95) mL: (5-10) mL: (18-26) g.
[0029] Furthermore, in step 3), the power of the ultrasonic dispersion is 200-300W.
[0030] Furthermore, in step 4), the usage ratio of the carboxylated aluminum oxide, N,N-dimethylformamide, N,N-dicyclohexylcarbodiimide, and silane coupling agent KH550 is (3-7) g: (50-80) mL: (1-2) g: (100-160) mL;
[0031] The power of the ultrasonic oscillation is 200-300W.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] In the present invention, polydopamine and silane coupling agent are used to synergistically modify titanium dioxide to improve its dispersibility in polymers. After polydopamine is coated on the surface of titanium dioxide, its surface presents a hydroxyl-rich structure, which provides more reaction sites for subsequent secondary modification and composite modification. At the same time, silane coupling agent is also used to modify nano-aluminum trioxide, and a carboxylation treatment is performed to reduce its surface energy and improve its dispersibility. After the carboxylated aluminum trioxide is subjected to secondary modification treatment, it is subjected to ball milling treatment with modified titanium dioxide to achieve physical combination, thereby obtaining composite nanoparticles. The composite nanoparticles have strong electron capture ability, which is beneficial to improving the breakdown voltage of the material and achieving the insulation effect of the material. In addition, styrene monomer and pentafluorostyrene monomer are used to modify nano-aluminum trioxide. The copolymerization of the two bodies is used to realize the synthesis of surface fluorinated polystyrene nanospheres, and then the surface of the basalt fiber is modified. Then, the composite nanoparticles and fluorinated styrene microspheres are coated on the basalt fiber through a surface coating method to obtain an insulating nanomaterial; after being introduced into the coating, the fluorine element can be introduced into the coating. Since the fluorine element has high electronegativity, the electrical insulation properties of the material can be improved by generating F-containing groups with deeper trap energy levels in the polymer, so that the coating has a high insulation effect after curing; moreover, the insulating nanomaterials are cross-linked in the coating to form a network skeleton structure, which can support and stabilize the structure of the coating, so that the coating has enhanced resistance to external forces and is not easy to be damaged, so that the coating has good stability and can maintain the ultra-high voltage insulation effect for a long time.
[0034] The room temperature curing water-based ultra-high voltage insulating coating of the present invention can improve the electrical insulation properties of the coating by adding insulating nanomaterials, so that the coating has a high insulating effect after curing, is not easily punctured when applied to electronic equipment, and has extremely high safety. Moreover, the insulating nanomaterials are cross-linked in the coating to form a network skeleton structure, which can support and stabilize the structure of the coating, thereby enhancing the coating's resistance to external forces and making it difficult to break, thereby making the coating stable and able to maintain the ultra-high voltage insulating effect for a long time. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the embodiment of the present invention, the dispersant is PX4585 (BASF), the antifoaming agent is A363 (Haichuan Chemical), the leveling agent is 57 (Haimingsi Chemical), the wetting agent is C-2817 (Haiyi Technology), the film-forming aid is ethylene glycol monobutyl ether, the thickener is AP425 (Haimingsi Chemical), and the curing agent is cuprous sulfate.
[0037] Example 1
[0038] A room temperature curable water-based ultra-high voltage insulation coating for electronics, the coating is formed by curing a water-based ultra-high voltage insulation coating at room temperature;
[0039] The water-based ultra-high voltage insulating coating is prepared from two components, A and B;
[0040] Component A includes the following raw materials in parts by weight: 50 parts of waterborne polyurethane resin, 5 parts of curing agent, 3 parts of polyetheretherketone ultrafine powder, 8 parts of insulating nanomaterials, and 20 parts of water;
[0041] Component B includes the following raw materials in parts by weight: 1 part of dispersant, 2 parts of antifoaming agent, 1 part of leveling agent, 1 part of wetting agent, 0.5 parts of film-forming aid, and 1 part of thickener;
[0042] The preparation method of water-based ultra-high voltage insulating coating comprises the following steps:
[0043] 1) stirring and mixing the waterborne polyurethane resin, polyetheretherketone ultrafine powder, insulating nanomaterial and water to obtain a mixture;
[0044] 2) The remaining raw materials are stirred and mixed, and then added into the mixture of step 1), and stirring is continued to obtain the water-based ultra-high voltage insulating coating.
[0045] The preparation method of the insulating nanomaterial is as follows:
[0046] 1) Weigh 10 g of titanium dioxide, disperse it in 200 mL of deionized water, stir and disperse it thoroughly, then add 0.3 g of tris(hydroxymethyl)aminomethane hydrochloride and 0.1 g of dopamine hydrochloride in sequence, stir at 8000 r / min for 4 h at 25 ° C. After the treatment is completed, wash it repeatedly with deionized water, dry it and grind it to obtain pretreated titanium dioxide;
[0047] 2) 1 mL of silane coupling agent KH550, 90 mL of anhydrous ethanol and 5 mL of deionized water were weighed, stirred at 80 ° C and 800 r / min for 10 min to obtain a mixed solution, and then 18 g of pretreated titanium dioxide was added, and magnetic stirring was continued at 80 ° C and 600 r / min for 3 h. After the treatment was completed, it was washed with deionized water, centrifuged, and dried to obtain modified titanium dioxide;
[0048] 3) Dissolve 1g of silane coupling agent KH550 and 2g of succinic anhydride in 60mL of N,N-dimethylformamide, stir at 80°C for 3h to obtain solution A, disperse 1g of nano-aluminum oxide in 60mL of N,N-dimethylformamide, ultrasonically disperse at 200W for 30min, then add 60mL of deionized water to obtain solution B, mix solution A and solution B in equal volumes, and stir magnetically at 40°C for 3h to obtain carboxylated aluminum oxide;
[0049] 4) 3 g of carboxylated aluminum oxide was added to 50 mL of N, N-dimethylformamide, and then ultrasonically vibrated at 200 W for 30 min. Then, the mixture was added to 100 mL of silane coupling agent KH550 together with 1 g of N, N-dicyclohexylcarbodiimide, and stirred at 300 r / min for 3 h at 40 ° C. Then, the mixture was centrifuged and dried, and then fully ball-milled with modified titanium dioxide at a mass ratio of 1:0.3 to obtain composite nanoparticles;
[0050] 5) 10 g of styrene containing 2% by mass of divinylbenzene, 110 mL of deionized water and 160 mL of anhydrous ethanol were mixed, stirred well, 0.3 g of potassium persulfate was added, and the mixture was reacted at 75° C. for 3 h. Then, 8 g of pentafluorostyrene containing 2% by mass of divinylbenzene was dripped into the reaction system using a constant pressure funnel within 30 min. The reaction was continued for 3 h. After the reaction was completed, the product was repeatedly washed with anhydrous ethanol after centrifugation and vacuum dried to obtain fluorinated styrene microspheres;
[0051] 6) The basalt fiber was placed in a Soxhlet extractor and extracted with acetone for 12 h. The fiber was then repeatedly washed with deionized water and dried to obtain pretreated basalt fiber. The composite nanoparticles were added to a container containing anhydrous ethanol and deionized water (mass ratio of 4:1) to obtain a suspension with a solid content of 0.5%. Fluorinated styrene microspheres accounting for 0.2% of the total mass of the suspension were then added. After 200 W ultrasonic oscillation for 30 min, the pretreated basalt fiber was added. After soaking at 50 ° C for 1 h, the fiber was dried at 50 ° C for 5 h to obtain an insulating nanomaterial.
[0052] Example 2
[0053] A room temperature curable water-based ultra-high voltage insulation coating for electronics, the coating is formed by curing a water-based ultra-high voltage insulation coating at room temperature;
[0054] The water-based ultra-high voltage insulating coating is prepared from two components, A and B;
[0055] Component A includes the following raw materials in parts by weight: 55 parts of waterborne polyurethane resin, 7 parts of curing agent, 5 parts of polyetheretherketone ultrafine powder, 10 parts of insulating nanomaterials, and 25 parts of water;
[0056] Component B includes the following raw materials in parts by weight: 1.5 parts of dispersant, 2.5 parts of antifoaming agent, 1.5 parts of leveling agent, 2 parts of wetting agent, 1.2 parts of film-forming aid, and 1.5 parts of thickener;
[0057] The preparation method of water-based ultra-high voltage insulating coating comprises the following steps:
[0058] 1) stirring and mixing the waterborne polyurethane resin, polyetheretherketone ultrafine powder, insulating nanomaterial and water to obtain a mixture;
[0059] 2) The remaining raw materials are stirred and mixed, and then added into the mixture of step 1), and stirring is continued to obtain the water-based ultra-high voltage insulating coating.
[0060] The preparation method of the insulating nanomaterial is as follows:
[0061] 1) Weigh 13 g of titanium dioxide, disperse it in 250 mL of deionized water, stir and disperse it thoroughly, then add 0.4 g of tris(hydroxymethyl)aminomethane hydrochloride and 0.1 g of dopamine hydrochloride in sequence, stir at 9000 r / min for 5 h at 26 ° C, and after the treatment is completed, wash it repeatedly with deionized water, dry it, and grind it to obtain pretreated titanium dioxide;
[0062] 2) 2 mL of silane coupling agent KH550, 93 mL of anhydrous ethanol and 7 mL of deionized water were weighed, stirred at 900 r / min for 20 min at 62 ° C to obtain a mixed solution, and then 23 g of pretreated titanium dioxide was added, and magnetic stirring was continued at 82 ° C and 650 r / min for 5 h. After the treatment was completed, it was washed with deionized water, centrifuged, and dried to obtain modified titanium dioxide;
[0063] 3) Dissolve 1.5 g of silane coupling agent KH550 and 3 g of succinic anhydride in 70 mL of N,N-dimethylformamide, stir at 82°C for 4 h to obtain solution A, disperse 2 g of nano-aluminum oxide in 70 mL of N,N-dimethylformamide, and add 70 mL of deionized water after 250 W ultrasonic dispersion for 40 min to obtain solution B, mix solution A and solution B in equal volumes, and stir magnetically at 42°C for 4 h to obtain carboxylated aluminum oxide;
[0064] 4) 5 g of carboxylated aluminum oxide was added to 70 mL of N, N-dimethylformamide, and then ultrasonically vibrated at 250 W for 40 min. Then, the mixture was added to 130 mL of silane coupling agent KH550 together with 1.5 g of N, N-dicyclohexylcarbodiimide, and stirred at 400 r / min for 5 h at 42 ° C. Then, the mixture was centrifuged and dried, and then fully ball-milled with modified titanium dioxide at a mass ratio of 1:0.5 to obtain composite nanoparticles;
[0065] 5) 15 g of styrene containing 2.5% of divinylbenzene by mass, 140 mL of deionized water and 180 mL of anhydrous ethanol were mixed, stirred well, 0.4 g of potassium persulfate was added, and the mixture was reacted at 76° C. for 5 h. Then, 10 g of pentafluorostyrene containing 2.5% of divinylbenzene by mass was dripped into the reaction system using a constant pressure funnel within 35 min. The reaction was continued for 4 h. After the reaction was completed, the product was repeatedly washed with anhydrous ethanol after centrifugation and vacuum dried to obtain fluorinated styrene microspheres;
[0066] 6) The basalt fiber was placed in a Soxhlet extractor and extracted with acetone for 13 h. The fiber was then repeatedly washed with deionized water and dried to obtain pretreated basalt fiber. The composite nanoparticles were added to a container containing anhydrous ethanol and deionized water (mass ratio of 4.2:1) to obtain a suspension with a solid content of 1%. Fluorinated styrene microspheres accounting for 0.5% of the total mass of the suspension were then added. After 250 W ultrasonic oscillation for 40 min, the pretreated basalt fiber was added. The fiber was soaked at 53 ° C for 2 h and dried at 55 ° C for 7 h to obtain an insulating nanomaterial.
[0067] Example 3
[0068] A room temperature curable water-based ultra-high voltage insulation coating for electronics, the coating is formed by curing a water-based ultra-high voltage insulation coating at room temperature;
[0069] The water-based ultra-high voltage insulating coating is prepared from two components, A and B;
[0070] Component A includes the following raw materials in parts by weight: 60 parts of waterborne polyurethane resin, 10 parts of curing agent, 7 parts of polyetheretherketone ultrafine powder, 13 parts of insulating nanomaterials, and 26 parts of water;
[0071] Component B includes the following raw materials in parts by weight: 2 parts of dispersant, 3 parts of antifoaming agent, 2 parts of leveling agent, 3 parts of wetting agent, 1.8 parts of film-forming aid, and 2 parts of thickener;
[0072] The preparation method of water-based ultra-high voltage insulating coating comprises the following steps:
[0073] 1) stirring and mixing the waterborne polyurethane resin, polyetheretherketone ultrafine powder, insulating nanomaterial and water to obtain a mixture;
[0074] 2) The remaining raw materials are stirred and mixed, and then added into the mixture of step 1), and stirring is continued to obtain the water-based ultra-high voltage insulating coating.
[0075] The preparation method of the insulating nanomaterial is as follows:
[0076] 1) Weigh 15 g of titanium dioxide, disperse it in 300 mL of deionized water, stir and disperse it thoroughly, then add 0.4 g of tris(hydroxymethyl)aminomethane hydrochloride and 0.2 g of dopamine hydrochloride in sequence, stir at 10000 r / min for 6 h at 28 ° C, and after the treatment is completed, wash it repeatedly with deionized water, dry it and grind it to obtain pretreated titanium dioxide;
[0077] 2) 3 mL of silane coupling agent KH550, 95 mL of anhydrous ethanol and 10 mL of deionized water were weighed, stirred at 1000 r / min for 30 min at 63 ° C to obtain a mixed solution, and then 26 g of pretreated titanium dioxide was added, and magnetic stirring was continued at 700 r / min for 6 h at 85 ° C. After the treatment was completed, it was washed with deionized water, centrifuged, and dried to obtain modified titanium dioxide;
[0078] 3) Dissolve 2g of silane coupling agent KH550 and 5g of succinic anhydride in 80mL of N,N-dimethylformamide, stir at 85°C for 5h to obtain solution A, disperse 3g of nano-aluminum oxide in 80mL of N,N-dimethylformamide, ultrasonically disperse at 300W for 50min, then add 80mL of deionized water to obtain solution B, mix solution A and solution B in equal volumes, and stir magnetically at 45°C for 5h to obtain carboxylated aluminum oxide;
[0079] 4) 7 g of carboxylated aluminum oxide was added to 80 mL of N, N-dimethylformamide, and then ultrasonically vibrated at 300 W for 50 min. Then, the mixture was added to 160 mL of silane coupling agent KH550 together with 2 g of N, N-dicyclohexylcarbodiimide, and stirred at 500 r / min for 7 h at 43 ° C. Then, the mixture was centrifuged and dried, and then fully ball-milled with modified titanium dioxide at a mass ratio of 1:0.8 to obtain composite nanoparticles;
[0080] 5) 16 g of styrene containing 3% by mass of divinylbenzene, 160 mL of deionized water and 200 mL of anhydrous ethanol were mixed, stirred well, 0.5 g of potassium persulfate was added, and the mixture was reacted at 78° C. for 6 h. Then, 12 g of pentafluorostyrene containing 3% by mass of divinylbenzene was dripped into the reaction system using a constant pressure funnel within 40 min. The reaction was continued for 5 h. After the reaction was completed, the product was repeatedly washed with anhydrous ethanol after centrifugation and vacuum dried to obtain fluorinated styrene microspheres;
[0081] 6) The basalt fiber was placed in a Soxhlet extractor and extracted with acetone for 15 h. The fiber was then repeatedly washed with deionized water and dried to obtain pretreated basalt fiber. The composite nanoparticles were added to a container containing anhydrous ethanol and deionized water (mass ratio of 4.5:1) to obtain a suspension with a solid content of 1.5%. Fluorinated styrene microspheres accounting for 0.6% of the total mass of the suspension were then added. After 300 W ultrasonic oscillation for 50 min, the pretreated basalt fiber was added. After soaking at 56 ° C for 3 h, the fiber was dried at 60 ° C for 10 h to obtain an insulating nanomaterial.
[0082] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain insulating nanomaterials.
[0083] Comparative Example 2: This comparative example is basically the same as Example 1, except that step 1) is omitted in the preparation of the insulating nanomaterial.
[0084] Comparative Example 3: This comparative example is basically the same as Example 1, except that in the preparation of the insulating nanomaterial, steps 1)-2) are omitted.
[0085] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the insulating nanomaterial.
[0086] Comparative Example 5: This comparative example is basically the same as Example 1, except that step 5) is omitted in the preparation of the insulating nanomaterial.
[0087] Test experiment:
[0088] Referring to QJ2220.1-1992 "Test Method for Electrical Insulation Performance of Coating", the methods provided in Examples 1-3 and Comparative Examples 1-5 were used to obtain insulating coating samples with a thickness of 60 μm, and then the insulation resistance and breakdown voltage of the coating were tested. The results are shown in Table 1.
[0089] Table 1
[0090] Example 1 Example 2 Example 3 Comparative Example 1 Insulation resistance / Ω <![CDATA[7.3×10 11 ]]> <![CDATA[8.1×10 11 ]]> <![CDATA[7.6×10 11 ]]> <![CDATA[8.4×10 5 ]]> Breakdown voltage / kV / mm 35.3 36.2 35.8 25.3 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Insulation resistance / ohm <![CDATA[3.5×10 9 ]]> <![CDATA[5.8×10 7 ]]> <![CDATA[1.7×10 7 ]]> <![CDATA[9.9×10 6 ]]> Breakdown voltage / kV / mm 30.1 28.6 27.9 26.8
[0091] It can be seen from Table 1 that the insulating coating in the present invention has a high insulation resistance value, a high breakdown voltage, and good electrical insulation performance.
[0092] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A room temperature curing water-based ultra-high voltage insulation coating for electronics, characterized in that: The coating is formed by curing water-based ultra-high voltage insulating paint at room temperature; The water-based ultra-high voltage insulating coating is prepared from two components, A and B; Component A includes the following raw materials in parts by weight: 50-60 parts of waterborne polyurethane resin, 5-10 parts of curing agent, 3-7 parts of polyetheretherketone ultrafine powder, 8-13 parts of insulating nanomaterials, and 20-26 parts of water; Component B includes the following raw materials in parts by weight: 1-2 parts of dispersant, 2-3 parts of antifoaming agent, 1-2 parts of leveling agent, 1-3 parts of wetting agent, 0.5-1.8 parts of film-forming aid, and 1-2 parts of thickener; The preparation method of the water-based ultra-high voltage insulating coating comprises the following steps: 1) stirring and mixing the waterborne polyurethane resin, polyetheretherketone ultrafine powder, insulating nanomaterial and water to obtain a mixture; 2) The remaining raw materials are stirred and mixed, and then added into the mixture of step 1), and stirring is continued to obtain the water-based ultra-high voltage insulating coating.
2. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 1, characterized in that: The curing agent is at least one of cuprous sulfate and cuprous nitrate.
3. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 1, characterized in that: The preparation method of the insulating nano material is as follows: 1) Styrene containing 2-3% of divinylbenzene by mass, deionized water and anhydrous ethanol are mixed, stirred well, potassium persulfate is added, and the mixture is reacted at 75-78° C. for 3-6 hours. Pentafluorostyrene containing 2-3% of divinylbenzene by mass is then dripped into the reaction system using a constant pressure funnel within 30-40 minutes. The reaction is continued for 3-5 hours. After the reaction is completed, the product is repeatedly washed with anhydrous ethanol after centrifugation and vacuum dried to obtain fluorinated styrene microspheres; 2) Put the basalt fiber into a Soxhlet extractor, use acetone to extract for 12-15 hours, then repeatedly wash with deionized water and dry to obtain pretreated basalt fiber, add the composite nanoparticles into a container containing anhydrous ethanol and deionized water to obtain a suspension, then add fluorinated styrene microspheres, add the pretreated basalt fiber after 200-300W ultrasonic oscillation for 30-50 minutes, soak at 50-56°C for 1-3 hours, and dry at 50-60°C for 5-10 hours to obtain an insulating nanomaterial.
4. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 3, characterized in that: In step 1), the usage ratio of styrene, deionized water, anhydrous ethanol, potassium persulfate and pentafluorostyrene is (10-16) g: (110-160) mL: (160-200) mL: (0.3-0.5) g: (8-12) g.
5. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 3, characterized in that: In step 2), the mass ratio of anhydrous ethanol to deionized water is (4.0-4.5):1; The solid content of the suspension is 0.5-1.5%; The added amount of the fluorinated styrene microspheres accounts for 0.2-0.6% of the total mass of the suspension.
6. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 3, characterized in that: The preparation method of the composite nanoparticles is as follows: 1) Weigh titanium dioxide, disperse it in deionized water, stir and disperse it thoroughly, then add tris(hydroxymethyl)aminomethane hydrochloride and dopamine hydrochloride in sequence, stir at 25-28° C. for 4-6 hours, and after the treatment is completed, wash it repeatedly with deionized water, dry it, and grind it to obtain pretreated titanium dioxide; 2) Silane coupling agent KH550, anhydrous ethanol and deionized water are weighed, stirred at 800-1000 r / min for 10-30 min at 60-63° C. to obtain a mixed solution, and then pretreated titanium dioxide is added, and magnetic stirring is continued at 80-85° C. and 600-700 r / min for 3-6 h. After the treatment is completed, the mixture is washed with deionized water, centrifuged, and dried to obtain modified titanium dioxide; 3) Dissolve 1-2g of silane coupling agent KH550 and 2-5g of succinic anhydride in 60-80mL of N,N-dimethylformamide, stir at 80-85°C for 3-5h to obtain solution A, disperse 1-3g of nano-aluminum oxide in 60-80mL of N,N-dimethylformamide, ultrasonically disperse for 30-50min, then add 60-80mL of deionized water to obtain solution B, mix solution A and solution B in equal volumes, and stir magnetically at 40-45°C for 3-5h to obtain carboxylated aluminum oxide; 4) Add carboxylated aluminum oxide to N,N-dimethylformamide, and after ultrasonic oscillation for 30-50 minutes, add it together with N,N-dicyclohexylcarbodiimide to silane coupling agent KH550, stir at 300-500 r / min for 3-7 hours at 40-43°C, then centrifuge and dry, and fully ball-mill with modified titanium dioxide in a mass ratio of 1: (0.3-0.8) to obtain composite nanoparticles.
7. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 6, characterized in that: In step 1), the ratio of the titanium dioxide, deionized water, tris(hydroxymethyl)aminomethane hydrochloride, and dopamine hydrochloride is (10-15) g: (200-300) mL: (0.3-0.4) g: (0.1-0.2) g; The stirring speed is 8000-10000 r / min.
8. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 6, characterized in that: In step 2), the usage ratio of the silane coupling agent KH550, anhydrous ethanol, deionized water, and pretreated titanium dioxide is (1-3) mL: (90-95) mL: (5-10) mL: (18-26) g.
9. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 6, characterized in that: In step 3), the power of the ultrasonic dispersion is 200-300W.
10. The room temperature curing water-based ultra-high voltage insulation coating for electronics according to claim 6, characterized in that: In step 4), the usage ratio of the carboxylated aluminum oxide, N,N-dimethylformamide, N,N-dicyclohexylcarbodiimide, and silane coupling agent KH550 is (3-7) g: (50-80) mL: (1-2) g: (100-160) mL; The power of the ultrasonic oscillation is 200-300W.
Citation Information
Patent Citations
Preparation method of polyurethane electronic and electrical insulating material
CN112706480A
Cited By
Ultraviolet-resistant antioxidant multi-layer composite drag reduction film and preparation method thereof
CN121271437A
Ultraviolet resistant antioxidant multilayer composite drag reduction film and preparation method thereof
CN121271437B